WORD FORMATION PROCESS OF NON-STANDARD VOCABULARYIN TWITTER STATUSES OF INDONESIAN DANGDUT SINGERS - Nisa, Rully Fakhrun (LANTERN (Journal on English Language, Culture and Literature), 2016)
Twitter is one of the media used by people to share their thoughts, to communicate, and torespond to others. Since Twitter users tend to communicate using spoken language, we canfind some new words created in order to make the communication more comfortable.Thepurpose of this study is to identify the word formation processes on twitter statuses ofIndonesian dangdut singers. This study uses Non-Participant Observation Method to collectthe data along with Reflective Introspective Identity and Translational Method to analyze thedata. The finding of this research shows 35 words from 11 twitter accounts that were analyzedin terms of the process of word formation. The processes that occurred are Derivation,Blending, Borrowing, Clipping and Acronym. Of these processes, borrowing is the mostcommon process of word formation found in the twitter statuses of dangdut singers becausethe singers tend to follow trend from Western since the borrowing words are mostly fromEnglish.